Chemically Engineered GaN Thin Films for Light‐Stimulated Artificial Synapses - Xiaoqin Yang; Jiawen Lu; Luyu Zhao; Xiaorui Han; Zhongwei Bai; Peiwen Quan; Liangshuai Xie; Liang Li; Haoxuan Sun; Mark Hermann Rummeli; Bingcheng Luo; Hong Gu (Advanced Photonics Research)
The conventional von Neumann architecture is increasingly losing the capacity to satisfy the urgent demand for high‐speed parallel computing, energy efficiency, and ultralow power consumption owing to the rapid growth of information. Brain‐inspired neuromorphic computing presents an opportunity to overcome the inherent limitations of conventional computers. In recent years, photoelectric neuromorphic devices have garnered significant attention for their potential applications in brain–machine interfaces, intelligent sensing, and neuromorphic computing. Herein, a simple two‐terminal light‐stimulated synaptic device is fabricated using GaN thin films through metal‐organic chemical vapor deposition. The device demonstrates the ability to mimic various biological synaptic functions, including learning‐experience behavior, the transition from short‐term to long‐term memory, paired‐pulse facilitation, and visual recognition and memory. In this research, an effective strategy for developing photonic synapses using GaN‐based materials in neuromorphic computing and bio‐realistic artificial intelligence systems is presented.